The Effect of Smooth Capitalism Dimensions on Consumer Culture Through Lifestyle Trends Among The Middle Class In Marbau Subdistrict - Syahreza S; Badaruddin B; Muba Simanihuruk; Harmona Daulay; Linda Elida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the effect of smooth capitalism dimensions on consumer culture through lifestyle trends among the middle class in Marbau Subdistrict. The dimensions of smooth capitalism examined in this study include digital platform penetration, algorithmic personalization, influencer marketing, and transaction convenience. This research employed an explanatory quantitative approach using a survey method involving 385 middle-class respondents who actively use digital platforms. The data were analyzed using SmartPLS 4. The findings show that digital platform penetration, algorithmic personalization, influencer marketing, and transaction convenience have a positive and significant effect on lifestyle trends. Lifestyle trends also have a positive and significant effect on consumer culture (? = 0.200; t = 3.920; p = 0.000) and are proven to mediate the effect of all smooth capitalism dimensions on consumer culture. The R-square values indicate that the model has strong explanatory power, namely 0.704 for lifestyle trends and 0.756 for consumer culture. These findings affirm that digital consumption among the middle class in Marbau is not merely an economic activity, but also a social practice related to identity, status, taste, and social recognition.